Synthesis of Novel 2',3'-Didehydro-2',3'-dideoxynucleoside - Singh Yadava, Virendra (Asian Journal of Chemistry, 2016)
The unsaturated nucleoside, viz., 2',3'-didehydro-2',3'-dideoxy-5-iodo-6-methyluridine 4 has been prepared via cyclic thionocarbonate 2 followed by deoxygenation.